2010
DOI: 10.1007/s12011-010-8894-8
|View full text |Cite
|
Sign up to set email alerts
|

Use of Stringent Selection Parameters for the Identification of Possible Selenium-Responsive Marker Genes in Mouse Liver and Gastrocnemius

Abstract: Selenium is a trace element that, although toxic in higher concentrations, is essential for human and animal health. In this study, we looked at microarray-based gene expression patterns from liver and gastrocnemius tissues in mice fed either a selenium-deficient diet or diets containing sodium selenite, selenomethionine, or a yeast-derived selenium supplement. A p value cutoff of 0.01 was used to identify a select set of selenium-responsive genes that were consistently differentially expressed across three ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 48 publications
1
8
0
Order By: Relevance
“…Our data provide further detail about the relationship between Se and male fertility and indicate that, besides being involved in the formation of normal sperm, Se is essential for the proper cell structure and maintenance of seminiferous tubule morphology. In addition, our data support previous findings that supplementation with different forms of Se results in common but mostly differential gene expression patterns regardless of tissue type [33,43,44]. Results from this study imply that Se may have an alternative, nonantioxidant role in male reproduction by helping to maintain testicular cell structure and function.…”
Section: Discussionsupporting
confidence: 89%
“…Our data provide further detail about the relationship between Se and male fertility and indicate that, besides being involved in the formation of normal sperm, Se is essential for the proper cell structure and maintenance of seminiferous tubule morphology. In addition, our data support previous findings that supplementation with different forms of Se results in common but mostly differential gene expression patterns regardless of tissue type [33,43,44]. Results from this study imply that Se may have an alternative, nonantioxidant role in male reproduction by helping to maintain testicular cell structure and function.…”
Section: Discussionsupporting
confidence: 89%
“…Plasma selenium concentrations were similar by GOLD stage, and selenium could not be assayed in lung tissue due to limited tissue mass. Prior studies also show that vitamin E and selenium contribute to gene regulation (10, 36-41, 48), hence we explored whether differences in nutrient status by disease stage had functional consequences by investigating whether genes responsive to vitamin E were differentially expressed by disease stage. Six of 42 vitamin E-responsive genes, namely KRT1, PPARG, TNNI2, KRT4, SULT2B1, and SRA1 , were differentially expressed by disease stage/severity, and there was evidence that genetic variation directly alters expression of the KRT1 gene in lung tissue.…”
Section: Discussionmentioning
confidence: 99%
“…Each nutrient-responsive gene list was curated for biologic relevance to the present study, and genes were retained if they were: known to be expressed in lung tissue, expressed under relevant physiologic concentrations of the nutrient, expression not limited to highly specific physiologic stress conditions, and not primarily related to cancer pathogenesis. (10, 36-48)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, we have demonstrated that the feeding of a 1:1 mix of inorganic and organic forms results in an equal assimilation of Se into blood [24,26] and liver [24] tissues as yielded by feeding only an organic form and that Seadequate cattle consuming equimolar amounts of Se in organic, inorganic, or mixed forms results in distinct liver transcriptome profiles [27]. With regard to the potential that the organic Se supplementation effect was due to the non-methyl Se portion of SeMet, research with mice has shown that equimolar supplementation of methionine versus SeMet results in differential hepatic transcriptome profiles [28,29]. Importantly, in these studies, mice also were fed an equal amount of non-selenium-enriched yeast, to control for possible inherent effects on transcriptional profiles by non-selenium yeast components.…”
Section: Introductionmentioning
confidence: 99%